Poder de la influencia, El: relaciones artísticas desde España a México - Lombardi, Melissa J., author; Leal, Francisco, advisor; Suárez-García, José Luis, advisor; Velasco, Marcela, committee member (Colorado State University. Libraries, 2012)
My research discusses the concept of "artistic partnership" through the pairing of various artists, ranging from Spain to Mexico. I propose that the power of influence present in each relationship is directly reflected in their work and that without such influence, they would have produced very different outcomes. Beginning with the Spanish poet, Federico García Lorca and his controversial "friendship" with the famous surrealist painter, Salvador Dalí, I expose the presence of one another in both poetry and painting. I continue on to research two lesser-known artists, Remedios Varo of Spain and Leonora Carrington of England who created a world of fantasy, magic and alchemy through a shared sense of whimsicality and lust for life. Their artwork is nearly identical both in theme and in style due to a profound understanding and appreciation for one another's uniqueness. My work ends with a radical proposal of a very different kind of relationship. Although Frida Kahlo is best known through her marriage to the Mexican muralist, Diego Rivera, her talent and passion for painting was never determined by him. I do not attempt to negate the presence of one another in their artwork but rather propose that this is not the type of influence that is fed by love and encouragement but rather that of a muse and her obsession. In conclusion, my research proposes that through these artistic partnerships, we are able to understand the difference between "interactions" and "bonds." I believe that the presence of each artist significantly modified the work of their partner and most importantly, allowed them to reach a level, both personally and artistically, that they would not have otherwise been able to reach on their own.
The power of influence: artistic partnerships from Spain to Mexico
Text in Spanish; title and abstract in English and Spanish.